Simplified model for the evaluation of the effects of explosions on industrial target. (September 2015) - Salzano, Ernesto; Basco, Anna
Abstract: The evaluation of vulnerability of process equipment to explosion is a central issue in the analysis of industrial risks. In this work, we have developed a simplified model, however based on fundamental equations, which includes structural and fluid–dynamic parameters for the target (the industrial equipment) and for the impacting pressure wave (shock waves) or object (fragment, debris) produced by different type of chemical explosions. The validity of methodology has been assessed by case histories. Several insights on the dynamic of structural interaction of the explosion with the target have been obtained, with specific reference to escalation effects. The model derives from the well-known Johnson's number, often adopted in impact engineering. Highlights: The evaluation of damage to target equipment may performed by the modified Johnson's damage number. Probability function (and probit coefficient) with respect to Johnson's damage number have been produced. Fragment, Vapor Cloud Explosion, and BLEVE have been analyzed in terms of cascading effects. Domino effects are analyzed with respect to the effects of explosions.